Ginkgo biloba Extract for Patients with Early Diabetic Nephropathy: A Systematic Review. (24th February 2013) - Zhang, Lei; Mao, Wei; Guo, Xinfeng; Wu, Yifan; Li, Chuang; Lu, Zhaoyu; Su, Guobin; Li, Xiaoyan; Liu, Zhuangzhu; Guo, Rong; Jie, Xina; Wen, Zehuai; et al.
Abstract : Objectives . To evaluate the effectiveness and safety of a Ginkgo biloba extract for patients with early diabetic nephropathy. Methods . Randomised controlled trials (RCTs) conducted on adults with early diabetic nephropathy which used Gingko biloba extract were included. The major databases were searched, and manufacturers of Gingko biloba products were contacted for information on any published or unpublished studies. Two authors independently extracted the data from the included studies. Data analysis was conducted using Review Manager 5.0 software. Results . Sixteen RCTs were included. Ginkgo biloba extract decreased the urinary albumin excretion rate (UAER), fasting blood glucose (FBG), serum creatinine (SCR), and blood urea nitrogen (BUN). The extract also improved hemorheology. The methodological quality in the included studies was low. The explicit generation of the allocation sequence was described in only 6 trials. None of the included trials were confirmed to use blinding. Three studies had observed adverse events. One study using angiotensin-converting enzyme inhibitor (ACEi) reported mild cough in both groups. No serious adverse effects were reported. Conclusions . Gingko biloba extract is a valuable drug which has prospect in treating early diabetic nephropathy, especially with high UAER baseline level. The safety for early diabetic nephropathy is uncertain. Long-term, double-blinded RCTs with large sample sizes are still needed to provide stronger evidence.